Analysis of Internal Control Over Merchandise Inventory at Suara Elektro Manado Store - Tangkere, Sheila Fabiola Scarlet; Alexander, Stanly W.; Weku, Priscillia (PT FORMOSA CENDEKIA GLOBAL, 2024)
Internal control is a process in an organization to check the accuracy, precision, and effectiveness and efficiency of a business process to achieve certain goals. This study aims to analyze the effectiveness of the implementation of internal control over merchandise inventory at Toko Suara Elektro Manado. The research method used in this thesis research is a descriptive method whose purpose is to analyze each data collected and then draw a conclusion. This research approach uses a qualitative research approach with a descriptive approach. The research results obtained by Toko Suara Elektro show a high dedication in managing inventory accurately and efficiently through the implementation of an integrated internal control system. This approach ensures effective risk control, optimal operational performance, and the store's ability to face challenges and changes responsively and adaptively